Three Novel Loci for Infant Head Circumference Identified by a Joint Association Analysis - Yang, Xiao-Lin; Zhang, Shao-Yan; Zhang, Hong; Wei, Xin-Tong; Feng, Gui-Juan; Pei, Yu-Fang; Zhang, Lei (Frontiers in Genetics, 2019)
As an important trait at birth, infant head circumference (HC) is associated with a variety of intelligence and mental related conditions. Despite being dominated by genetics, the mechanism underlying the variation of HC is poorly understood. Aiming to uncover the genetic basis of HC, we performed a genome-wide joint association analysis by integrating the genome-wide association summary statistics of HC with that of its two related traits birth length and birth weight, using a recently developed integrative method MTAG, and performed in silico replication in an independent sample of intracranial volume (N=26,577). We then conducted a series of bioinformatic investigations on the identified loci. Combining the evidence from both the MTAG analysis and the in silico replication, we identified 3 novel loci at the genome-wide significance level (α=5.0×10-8): 3q23 (lead SNP rs9846396, pMTAG=3.35×10-8, preplication=0.01), 7p15.3 (rs12534093, pMTAG=2.00×10-8, preplication=0.004) and 9q33.3 (rs7048271 pMTAG=9.23×10-10, preplication=1.14×10-4). Each of the 3 lead SNPs was associated with at least one of 8 brain related traits including intelligence and educational attainment. Credible risk variants (CRVs), defined as those SNPs located within 500 kb of the lead SNP and with p-values within two orders of magnitude of the lead SNP, were enriched in DNase I hypersensitive site (DHS) region in brain. Nine candidate genes were prioritized at the 3 novel loci using multiple sources of information. Gene set enrichment analysis identified one associated pathway GO:0048009, which participates in the development of nervous system. Our findings provide useful insights into the genetic basis of HC and the relationship between brain growth and mental health.